2002
DOI: 10.1088/0964-1726/11/4/312
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and validation of a mathematical model for traveling wave ultrasonic motors

Abstract: The derivation of a mathematical model for traveling wave ultrasonic motors and its experimental validation are reported. In a first step, the motor was structured into subsystems and models for the individual components were derived, simplified and described mathematically. The resulting submodels were then joined into an overall unified model of the motor, which allows us to study the impact of diverse motor parameters and control variables on the motor performance. In order to validate the model, systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 12 publications
4
23
0
Order By: Relevance
“…In the second stage, high-frequency oscillatory vibrations of the stator are transformed into unidirectional microscopic motion of the rotor. Several references concerning the working principle of piezoelectric ultrasonic motors are given in [10].…”
Section: Working Principle and Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second stage, high-frequency oscillatory vibrations of the stator are transformed into unidirectional microscopic motion of the rotor. Several references concerning the working principle of piezoelectric ultrasonic motors are given in [10].…”
Section: Working Principle and Experimental Setupmentioning
confidence: 99%
“…It is shown that the effect acts on the starting state as well as on the settling state. In order to validate the model, the simulation results are compared with results measured by Kandare and Wallaschek [10] on the Daimler-Benz AWM90-X motor using the test bench described in Fig. 1(a) and are compared with the ones measured by Thomas Schulte and Norbert Fröhleke [11] on a prototype USM(AWM-90).…”
Section: Introductionmentioning
confidence: 99%
“…The authors attempt to estimate the theoretical limit of motor performance from the point of view of the friction control mechanism. The derivation of a mathematical model for traveling wave USMs and its experimental validation has been reported by Kandare and Wallaschek [14]. The motor has been structured into subsystems and models for the individual components have been derived, simplified and described mathematically in their study.…”
Section: Ultrasonic Motorsmentioning
confidence: 99%
“…Since the modern controls are hard to be applied on USM, PID controller has been widely used in USM applications (4)(5)(6)(7) . However, there are limitations of the control performance using the conventional fixed-gain type PID controller because USM causes serious characteristic changes during operation and contains non-linearity.…”
Section: Introductionmentioning
confidence: 99%